Analisa Pengaruh Karakteristik Perusahaan terhadap Tingkat Pengungkapan Tanggung Jawab Sosial Perusahaan pada Perusahaan High Profile yang Tercatat di Bursa Efek Indonesia pada Tahun 2005-2007 - Yusuf, Muhammad (Bina Nusantara University, 2011)
This research is to examine corporate social responsibility disclosure and its level in Indonesian companies. Based on a review of previous researches, six independents variables are extracted for a multiple regression analysis. They are company size, profitability, age, leverage, liquidity, and public ownership. The technique for examining multiple regression analysis by using spss 11,5 programs. Samples of this research are 41 high profile companies that listed in Indonesia Stock Exchange in 2005, 2006, and 2007 acquired using purposive sampling method. The results of this research sowed that on significance rate of 5%, the company size, age, leverage, and liquidity has a significance effect with corporate social responsibilities disclosures. While for the profitability and public ownership has no effect with corporate social responsibilities. These results generally coincide with previous research findings on corporate social responsibilities disclosures.